A Analisis Kesalahan Kalimat Pada Skripsi Mahasiswa Sosiologi Universitas Malikussaleh - Nasya Juar Riski Ramadhan; Safriandi; Emilda (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe sentence errors in the Sociology Student Thesis at Malikussaleh University.  This study uses a qualitative method.  This research uses reading and record techniques.  This research data is a sentences in the thesis of Sociology Student Malikussaleh University.  The data source of this research is the Sociology Student Thesis at Malikussaleh University totaling 7 theses in 2024. Data collection methods using instruments in the form of data cards.  Data analysis is carried out by collecting data, reducing, presentation, and data conclusions.  The results showed that there were sentence errors in the Sociology Student Thesis at Malikussaleh University as many as 140 sentences.  Errors are divided into 5 parts, namely: (1) sentence elements must be clear (a) 45 sentences of non-subject sentences, (b) sentences of not predicated as many as 13 sentences, (c) sentences as many as 9 sentences.  (2) Sloor or Paragelan as many as 10 sentences, (3) Throughing sentences as many as 10 sentences, (4) 5 sentences, (5) impartial as many as 13 sentences.